2022
DOI: 10.2215/cjn.15551121
|View full text |Cite
|
Sign up to set email alerts
|

Association of Mitochondrial DNA Copy Number with Risk of Progression of Kidney Disease

Abstract: Background and objectivesMitochondrial DNA copy number is a biomarker of mitochondrial function, which has been hypothesized to contribute to pathogenesis of CKD through podocyte injury, tubular epithelial cell damage, and endothelial dysfunction. The prospective association of mitochondrial DNA copy number with CKD progression has not been previously evaluated.Design, setting, participants, & measurementsChronic Renal Insufficiency Cohort study participants had serum levels of mitochondrial DNA copy numbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
10
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 37 publications
(54 reference statements)
0
10
2
Order By: Relevance
“…Diverse approaches to maintain mitochondrial function include the regulation of ROS metabolism, antagonism of mitochondrial oxidants, promotion of mitochondrial biogenesis and ATP synthesis, inhibition of mitochondrial fragmentation, and inhibition of the mitochondrial permeability transition pore. Studies like the one published by He et al (4) encourage us to pursue such approaches and lend further support to the hypothesis that maintaining mitochondria homeostasis may prevent kidney pathogenesis and disease progression.…”
mentioning
confidence: 64%
See 3 more Smart Citations
“…Diverse approaches to maintain mitochondrial function include the regulation of ROS metabolism, antagonism of mitochondrial oxidants, promotion of mitochondrial biogenesis and ATP synthesis, inhibition of mitochondrial fragmentation, and inhibition of the mitochondrial permeability transition pore. Studies like the one published by He et al (4) encourage us to pursue such approaches and lend further support to the hypothesis that maintaining mitochondria homeostasis may prevent kidney pathogenesis and disease progression.…”
mentioning
confidence: 64%
“…Moreover, in GCKD, a low mitochondrial DNA copy number was a predictor of all-cause mortality (6). In contrast, He et al (4) found no difference in the prevalence of cardiovascular disease or diabetes mellitus in the three tertiles of mitochondrial DNA copy number in the CRIC study, nor did they find an association of mitochondrial DNA copy number with mortality.…”
mentioning
confidence: 84%
See 2 more Smart Citations
“…A later study in chronic renal insufficiency cohort reported that the lower mtDNA copy number was correlated with a higher risk of CKD progression, independent of established risk factors in CKD patients [ 62 ]. mtDNA release in platelets driven by a receptor for immune complex FcγRIIA is the key source of mitochondrial antigens in systemic lupus erythematosus [ 7 ].…”
Section: Mtdna Distribution In Kidney Diseasesmentioning
confidence: 99%